Literatur Review Faktor-Faktor yang Mempengaruhi Kejadian Insomnia - Ila Nabila Safiroh; Dona Yanuar Agus Santoso; Livana PH; Yulia Susanti (SEHATI: Jurnal Kesehatan, 2026)
Insomnia sleep disorders can lead to long-term health issues if not promptly addressed and can significantly impact an individual's quality of life, including work performance and social relationships. Furthermore, it increases the risk of health problems such as depression, anxiety, cardiovascular disease, obesity, and diabetes. This review article aims to identify the factors that influence the occurrence of insomnia. This study utilizes a literature review design with a descriptive analysis technique, examining 17 journals published within the last 5 years. The search was conducted on Google Scholar using keywords such as "insomnia," "causes," and "factors," focusing on published literature. The findings indicate that insomnia can be influenced by various factors, including gadget use, stress, anxiety, caffeine consumption, and medical conditions such as hypertension, breast cancer, obesity, and rheumatoid arthritis. Based on the literature review, it can be concluded that insomnia is caused by various factors, which are categorized into three groups: psychological, lifestyle, and biological factors. Psychological factors include anxiety and stress; lifestyle factors include caffeine consumption and gadget use; and biological factors include the physical conditions of individuals experiencing disorders such as breast cancer, obesity, hypertension, and rheumatoid arthritis